Construction of Ecological Water Resources Management Leadership Model Based on Multi-Agent Collaboration - Meng, Meng (Water resources management, 2024)
Due to the quick economic growth, our country's water pollution has worsened to a critical level; the water crisis, due to the lack of water resources and severe pollution, is now a major obstacle impacting economic growth, public health, and social stability. This underscores the urgent need for ecological water resources management. In this context, this paper introduces evolutionary game theory from the perspective of multi-agent cooperation. It constructs a game model to analyse the relationship between various entities in ecological water resources governance. Then, from the government's perspective, a leadership model of ecological water resources governance is built. The research results reveal that for polluters, there is a consistent tendency to avoid treating pollutants, especially when the cost of treatment is high. However, any watershed governance measure must take into account the interest mechanism of the grass-roots government. Therefore, it is crucial to consider the relationship of interest among various subjects from multiple angles and in an all-around way and build a leadership model that can adapt to different requirements with the government as the main body. This approach can lead to a significant improvement in water treatment effectiveness.